Средиземноморские элементы в фауне жужелиц (Coleoptera, Carabidae) Украины - Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1968)
176 species of Carabidae (22.7%) out of 775 ones, inhabiting the Ukraine, are the species of the Mediterranean origin. Depending on the areals they are united in six groups: the Mediterranean proper (90 species), the east Mediterranean (48 species), the old Mediterranean (18 species), the Crimea-Caucasus (5 species), the Crimea-Balkan (1 species) and the Crimean endemics (14 species). The spreading of these species and areas typical for them as well as new locations for some of the species are mentioned in the article.